From Enlightenment to Equality: Spirituality May Lead the Way to a Gender Just Society in India and Beyond - ERIN SMITH (Dr. Chinmay Pandya, 2015)
India is a country of spiritual traditions and paradoxes. Its spiritual verve offers sustenance through personal transformation, truth, harmony, and connection, yet today large numbers of people in India struggle against poverty, abuses, injustice, and inequalities. India is a land of daughters, known for their valour, hope, knowledge, and wealth of spirit, yet today the status of women is one of the country's greatest challenges and gender equality is fighting an often-silent battle. This study was conceived from the notion that Indian spirituality, in its truest essence, is the antithesis to this gender paradigm, and accordingly, it examined if spirituality can work to achieve a more gender equal and just society. Organized with the support of Dev Sanskriti University, this pilot study sought to uncover a correlation between participants' spirituality and their beliefs about gender roles, their gender equal attitudes, and gender equal behavior in the home. Though findings revealed no exceptional correlation, results identified a relationship between spirituality and gender equality within which gender discourse should focus and further research should follow. Gender inequality is pervasive in all countries, and such a global crisis deems further exploration into spirituality and gender equality not only compelling but also necessary.